Proteasomal degradation of herpes simplex virus capsids in macrophages releases DNA to the cytosol for recognition by DNA sensors - BOWIE, ANDREW (My University, 2013)
The innate immune system is important for control of infections, including herpesvirus infections. Intracellular DNA potently stimulates antiviral IFN responses. It is known that plasmacytoid dendritic cells sense herpesvirus DNA in endosomes via TLR9 and that nonimmune tissue cells can sense herpesvirus DNA in the nucleus. However, it remains unknown how and where myeloid cells, such as macrophages and conventional dendritic cells, detect infections with herpesviruses. In this study, we demonstrate that the HSV-1 capsid was ubiquitinated in the cytosol and degraded by the proteasome, hence releasing genomic DNA into the cytoplasm for detection by DNA sensors. In this context, the DNA sensor IFN-γ-inducible 16 is important for induction of IFN-β in human macrophages postinfection with HSV-1 and CMV. Viral DNA localized to the same cytoplasmic regions as did IFN-γ-inducible 16, with DNA sensing being independent of viral nuclear entry. Thus, proteasomal degradation of herpesvirus capsids releases DNA to the cytoplasm for recognition by DNA sensors.
PUBLISHED
Keywords: Immune System; Immunology, Inflammation & Infection